Frozen fraction of field blind samples from Antarctica, Neumayer Station III, measured with the Leipzig Ice Nucleating Array - Eckermann, Oliver; Wex, Heike; Jurányi, Zsófia; Weller, Rolf; Henning, Silvia (In: Eckermann, O et al. (2025): INP data from Antarctica, Neumayer Station III, during two years [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974187, 2025)
Ice nucleating particles (INPs) are important atmospheric particles influencing the formation of ice in clouds. Their sources and atmospheric concentrations currently are subject of plenty of research. The here provided data on INPs (Ice Nucleating Particles) were derived from particles collected onto filters at the German Antarctic Neumayer Station III in Queen Maud Land, East Antarctica continuously for two years from December 2019 until December 2021. Filters were analyzed at the TROPOS ice-lab in Germany using well established off-line techniques. Detailed information on sampling and data evaluation are given in the abovementioned publication which this data-set accompanies. Measured frozen fractions are provided for samples, field blinds and heated samples, INP concentrations are provided for samples both with and without subtracting the background.
Keywords: Antarctica; ice nucleating particles (INP); Neumayer Station